LANDFILL GAS FOR ENERGY: ITS STATUS AND PROSPECT IN INDONESIA - Kardono Kardono (Jurnal Teknologi Lingkungan, 2008)
Indonesia, a nation with more than 230 million population, is the world’s largest archipelagic state located between Asia and Australia continents. In 2000, the production of municipal solid waste (MSW) or refuse in 384 Indonesian cities was about 80,235 tons or 320,940 m3 per day. Refuse generation is predicted to increase five times by 2020. Waste composition is influenced by external factors, such as geographical location, the population’s standard of living, energy source, and weather. Generally, ahigh percentage of organic matter of refuse is between 61 and 72 per cent by weight. The presence of paper, plastic, glass, and metal ranges from 0.4 to 13 per cent. The current handling of refuse in Indonesia is mostly used the disposal land of unhealthy landfill in the form of open dumping. Around 450 units of open dumping have been in operation in Indonesian big cities. These open dumping landfills cause some problems ranging from odor to health problems. Center of Environmental Technology, BPPT has been preparing to carry out landfill mining both for its compost and gas. The gassampling must be done first before it is pumped for energy use. The gas is suggested to be utilized for generating energy, for example for electricity. Initial test indicated that the composition of methane gas (CH4) is around 50%, which is a good enough for energy generation. If the percentage of burnable gas is too low to be used for generating electric energy, it might be mixed with high content of heating value of natural gas (dual fuel system). This paper will present the conditions of open dumping of landfill inIndonesia, and the status and the distribution of its containing gas. From this knowledge of the amount and distribution of landfill gas, it will be analyzed for suggestion how the mined gas will be suitably utilized by the people.